The influence of mature oak stands and spruce plantations on soil-dwelling click beetles in lowland plantation forests - Tereza Loskotová; Jakub Horák (PeerJ, 2016)
Most European forests have been converted into forest plantations that are managed for timber production. The main goal of this paper was to determine the difference between mature native sessile oak (Quercus petraea) stands and non-indigenous Norway spruce (Picea abies) plantations, with respect to communities of Athous click beetles in approximately 6,500 ha of lowland plantation forest area in the Czech Republic. Athous subfuscus was the most abundant and widespread species, followed by A. zebei and A. haemorrhoidalis, while A. vittatus was considered rare. Spatial analysis of environmental variables inside studied patches showed that the species composition of Athous beetles best responded to a 20 m radius surrounding traps. The species’ responses to the environment showed that A. vittatus and A. haemorrhoidalis preferred oak stands, while A. zebei and A. subfuscus were associated with spruce plantations. In addition, oak stands showed higher diversity of beetle communities. The studied species are important for their ecosystem services (e.g. predation on pests or bioturbation) and seem to tolerate certain degrees of human disturbances, which is especially beneficial for forest plantations managed for timber production.